Doses and forms of Azospirillum brasilense inoculation on maize crop - Santini, Jose M. K.; Buzetti, Salatier [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Galindo, Fernando S. [UNESP]; Coaguila, Daniel N.; Boleta, Eduardo H. M. [UNESP] (Univ Federal Campina Grande, 2018)
In search of a more sustainable agriculture, the use of beneficial microorganisms has been highlighted, because they are low-cost and can reduce the use of fertilizers and increase grain yield. The present study aimed to evaluate the efficiency of A. brasilense inoculation and the best form and dose of inoculation in maize, measuring the impact on some physical characteristics and on its nutrition. The experiment was conducted in a greenhouse, in Ilha Solteira, SP, Brazil, in a completely randomized design, with four replicates and eight treatments: 1) control; 2) Seed lx; 3) Seed 2x; 4) Soil lx; 5) Soil 2x; 6) Leaf lx; 7) Leaf 2x; 8) Seed lx + Leaf lx, respectively representing in each treatment the site and dose of application ( lx, dose recommended by the manufacturer; 2x, twice the dose recommended by the manufacturer). No differences were found in any physical characteristics evaluated between treatments; however, for nutrient contents in the leaf tissue, there was effect on Zn content. It was concluded that, regardless of the presence of A. brasilense inoculation, forms or dose (in hybrid DKB 350), in general, there were no improvements in the characteristics evaluated.
Keywords: diazotrophic bacteria; plant growth promoters; plant nutrition; Zea mays L.